A COMPARATIVE CLINICAL EVALUATION OF THE EFFICACY OF MADHUMEHA NASHINI GUTIKA & DARVYADI KWATH IN MADHUMEHA W.S.R. TO DIABETES MELLITUS - Bhawana, Sharma; Dinesh Kumar, Goyal (International Journal of Ayurveda and Pharma Research, 2015)
Diabetes has become a dreadful disease in this era. It is also described in Ayurvedic texts in terms of Madhumeha. Diabetes Mellitus is disease known from the dawn of civilization. Sedentary life style, lack of exercise, faulty dietary habits, improper medication & urbanization precipitate the disease. It is estimated that the total number of people with diabetes will rise from 171 million in 2000 to 366 million by 2030. As per WHO report, currently half a billion people (12% of the worlds population) are considered obese. As obesity is the one of the root cause of the disease. Observing the current status of prevalence and morbidity of the disease proper medication for the disease is mandatory. In the present study, Madhumeha Nashini Gutika a herbomineral preparation and Darvyadi Kwath (both mentioned in Ayurvedic texts) were selected for clinical trial. The study comprised of a series of 60 patients of Madhumeha. The patients were selected from OPD and IPD of Kayachikitsa of Rishikul Government Ayurvedic P.G. College & Hospital. After evaluating the total effect of therapies it was observed that the Madhumeha Nashinh Gutika & Darvyadi Kwath (Combined therapy) provided better relief to the patients of Madhumeha in comparison to single group therapy.